Plasmon-Assisted Selective Enhancement of Direct-Band Transitions in Multi-Layer MoS2 - Tejendra Dixit; Ankit Arora; Miryala Muralidhar; Masato Murakami; Pramoda K. Nayak; Kolla Lakshmi Ganapathi; M. S. Ramachandra Rao (IEEE Photonics Journal)
Multi-layer MoS2 offers numerous advantages over mono-layer MoS2 in terms of improved absorption, enhanced emission and high optical density of states, which make it a better candidate for devices. However, the selective tuning of the direct-band emissions in multi-layer MoS2 is essential for various optoelectronic applications. In this work, we have demonstrated a systematic tuning of direct-band transitions in multi-layer MoS2 using Au coating prepared by sputtering and e-beam evaporation. We observed nearly 80-fold enhancement in the ratio of direct-to indirect-peak intensity with Au coating (e-beam) to that of the direct-to indirect-peak intensity of pristine samples. Along with that, complete quenching in the emissions corresponding to I-valley has been observed with Au coating. This work provides new dimensions towards the realization of plasmonic/optoelectronic devices based on multi-layer MoS2.